Policy for Empowering Technology-Based Startup Companies within University-Based Incubators - Mulyana, Ardiyan Rofiq; Putra, R. Ahmad Romadhoni Surya; Djunaedi, Achmad; Faristasari, Selvi (Transpublika Publisher, 2025)
Technology‑based startups play a critical role in driving innovation and economic growth, yet they remain highly vulnerable to early failure due to limited capital, weak managerial capacity, and insufficient market access. University‑based business incubators have emerged as strategic ecosystems to nurture these startups by providing facilities, mentoring, training, and access to research networks and funding. This study aims to analyze the effectiveness of university business incubator policies in strengthening technology‑based startup companies, using the 7S framework (Space, Shared, Service, Support, Skill Development, Seed Capital, and Synergy) as the analytical lens. An exploratory sequential mixed‑methods approach was employed, beginning with qualitative interviews and observations, followed by quantitative surveys of 40 tenants (20 from a public university and 20 from a private university). The integrated findings reveal that the public university incubator (UGM) demonstrates stronger performance in service, support, skill development, and synergy, while the private university incubator (UII) shows relative advantages in space, shared facilities, and seed capital. Although all seven policy factors are generally effective, their priority differs across institutional contexts. These results highlight the need for differentiated policy design that recognizes the distinct strengths of public and private university incubators, while establishing the 7S framework as a national benchmark for evaluating startup incubation policies.